The influence of post-annealing temperature on indium-silicon oxide thin film transistors. (July 2022) - Arulkumar, S.; Parthiban, S.; Kwon, J.Y.
Abstract: The room temperature sputtered Indium silicon oxide (ISO) thin-films were post annealed at various temperatures and studied for thin-film transistor (TFT) active channel layer application. The structural and optical properties of as-deposited and post-annealed ISO thin-films were analysed. XRD and HRTEM analysis revealed transformation of ISO thin film from amorphous nature to polycrystalline nature when post-annealed above 150 °C. The surface topography analysis indicated the presence of smooth surfaces for all ISO thin-films. ISO thin-films exhibited the average visible transmittance of 87% regardless of post-annealing temperature. The highest saturation mobility of 39.1 cm 2 /V.s was achieved for ISO TFT post-annealed at 200 °C. The obtained results show that post annealing temperature has significant influence on ISO TFT properties.